2018
DOI: 10.18843/ijcms/v9i1/14
|View full text |Cite
|
Sign up to set email alerts
|

Global Scenario of Self Medication: A Review of Literature

Abstract: Self

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In India, the majority of the population consults community pharmacists for their minor illnesses and avoid visiting doctors for minor illnesses. Hence, a similar finding was seen in a few prior studies [13,20]. The study conducted in Manipal University, Mangalore was reported that the most common reason for self-medication reported by a large number of participants was the illness being too trivial and lack of time to consult a doctor [21].…”
Section: (51%)supporting
confidence: 79%
“…In India, the majority of the population consults community pharmacists for their minor illnesses and avoid visiting doctors for minor illnesses. Hence, a similar finding was seen in a few prior studies [13,20]. The study conducted in Manipal University, Mangalore was reported that the most common reason for self-medication reported by a large number of participants was the illness being too trivial and lack of time to consult a doctor [21].…”
Section: (51%)supporting
confidence: 79%
“…Jafari et al, in 2015, reported a significant correlation between self-medication and the education level of the participants 18 . Similarly, Garofalo et al, in 2015, found education level to be significantly associated with selfmedication of the respondents 20 .On the contrary, Kulkarni et al, in 2018 did not report education level to be associated with self-medication of patients 24 . If such an association exists, it is debatable whether people with low education or higher education do more selfmedication.…”
Section: Frequency Of Self-medication and Its Associated Factors Amon...mentioning
confidence: 96%
“…In various studies, numerous factors have been introduced to predict self-medication behaviors, including age, sex (7), marital status, depression, activity limitation, life satisfaction (10), education level, income level, place of residence and awareness level (16), past experiences of selfmedication and self-assessment of health status (17), cost saving (18), smoking and alcohol drinking, chronic illness, self-efficacy, and low drug literacy (17). Health literacy is associated with the ability of individuals to acquire, understand, and use information for health promotion (19), the situation that happens during the self-medication process according to most researchers; therefore, it seems that health literacy level is a determining factor in the occurrence of self-medication behaviors (20,21).…”
Section: Introductionmentioning
confidence: 99%